Accelerating autism diagnosis using asynchronous telehealth technology - Reischl, Uwe; Morrier, Michael; Mitchell, Gwen; Oberleitner, Ron (International Journal Of Community Medicine And Public Health, 2023)
Background: Early identification and treatment of autism can prevent additional behavioral problems later in a child’s life. Long wait lists and travel limitations can often make it difficult for parents to obtain timely evaluations. A new telehealth technology has been developed that can provide clinicians with the ability to remotely observe a child’s behavior at home and allows parents to communicate with the clinician directly. The objective of this study was to compare the length of time from referral to the completion of a child’s diagnostic evaluation using asynchronous telehealth (TH) and using the traditional in-person assessment method (IPA). Methods: Three tertiary autism diagnostic centers in the United States conducted this study between 2016 and 2018. All three institutional review boards approved the research. Twenty-eight children were assigned to an IPA group and 29 children were assigned to a TH group. The IPA assessment was based on a standard in-person evaluation. Telehealth assessments used the naturalistic observation diagnostic assessment (NODA) system. Data were analyzed using SPSS. Required sample size was determined by power analysis. Results: For the three diagnostic centers, the average time from referral to completion of an autism diagnosis with IPA was 115 days and 66 days with telehealth. Conclusions: The NODA TH video-capture smartphone‐based technology offered a significant timesaving advantage for families seeking autism diagnostic services. The TH technology provided families located in remote areas with easier access to autism evaluations.